Путеводитель по растениям Удмуртии: [справочник] / В. В. Туганаев, Г. Р. Платунова, В. В. Булатов - Туганаев Виктор Васильевич (Удмуртия, 2020)
Экземпляры: ф.1 (20200918) / Инвентарный номер: 60299 / Цена: / Сис.шифр: 41.8(2Рос.Удм) / Авт.знак: Т 81 / ГРНТИ: 68.35.43 / ББК: 41.8(2Рос.Удм)я2